The regulation of equity crowdfunding in Malaysia. - Hingun, Mohsin; Mohd. Sulaiman, Aiman @ Nariman (2016)
The power of the internet to connect various interest groups has spawned novel ways of conducting transactions giving rise to the genesis of new service providers who aspire to unlock the potential of emerging business models in the electronic marketplace. Equity crowdfunding, an important form of crowdfunding enables the ‘crowd’ on the internet to finance new business ventures and start ups through online crowdfunding platforms in exchange for equity in the business. The objective is to gain access to an unprecedented source of capital created by the small contributions of members of the public. The inherent risk of investors losing money in new business ventures coupled with the increasing incidence of fraudulent online schemes call for regulatory measures to protect the investors in addition to facilitating the provision of the service. Malaysia has laid down the legal foundations for the provision and regulation of this new form of fundraising through the 2015 amendment to the Capital Markets and Services Act 2007 and the issue of Guidelines on Regulation of Markets. The objective of this paper is to analyse the legal provisions and guidelines governing issuers seeking finance, the platforms providing the electronic facilities and the protection of investors wishing to invest in equity crowdfunding. Reference will be made to the more active global crowdfunding jurisdictions with a view to drawing valuable lessons on how Malaysia, one of the earliest Asian countries to offer this service could enhance its existing legal regime.